VARIATION TEACHING METHOD OF PRE-SERVICE TEACHER IN MICRO-TEACHING CLASS - Sani, Rini Dwitya; Asty, Herfyna; Mega Putri, Dian; Noviani Syafar, Dian (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Nasional, 2022)
This research was based by the interest of researchers to find the methods used by prospective PI English teachers in Padang. The purpose of this research is to find out what methods are used by prospective English teachers . The implementation uses several methods in learning, especially in learning English. This research is a qualitative research. The instrument used is an observation checklist. Data was collected from micro teaching video recordings which were then analyzed based on the observation checklist. The observation checklist is based on the Discover Learning and Problem-Based Learning methods which are then analyzed for the learning process in the recording. The results of this study were found that as many as 8 prospective teachers used Discovery Learning in learning while 2 prospective teachers used Problem-Based Learning in learning in the Micro Teaching class. The conclusion of this study is that all the learning carried out by prospective English teachers is good even though they use different methods. The suggestion is that prospective English teachers should be able to teach it in every phase of the learning method so that the learning objectives can be achieved.